The fossil rodent faunas of the localities Alcoy 2C and 2D (Alcoy Basin, Spain). Implications for dating the classical locality of Alcoy-Mina - Mansino, S.; Fierro, I.; Ruiz-Sánchez, F.J.; Montoya, P. (Journal of Iberian Geology, 2013)
In the Gormaig area (Alcoy basin, SE Spain) a number of fossil mammal localities are known, of which only the classic site of Alcoy-Mina, known since the mid-19th century, has yielded remains of macrofauna. In the vicinity of this site are the localities of Alcoy-2C (AL2C) and Alcoy-2D (AL2D), probably representing the levels of Alcoy-Mina. The faunal assemblage allows dating the AL2C and AL2D localities as Early Pliocene (end of the Early Ruscinian or early-late Ruscinian boundary, MN14-MN15). Several taxa (Pliopetaurista and Glis) are thought to have affinities for humid and close biotopes.